About mechanisms of the formation of surface laser-induced structures - Trokhimchuck, Petro P. (Journal of the Belarusian State University. Physics, 2018)
The problems of the mechanisms the formation of laser-induced surface structures are discussed. A detailed analysis of the formation of such structures on silicon and germanium is carried out. The influence of the spectral characteristics, pulses number of irradiation and matter on the geometric dimensions of the received structures and on their phase states is shown. An analysis is made of the possibility of applying the Chandrasekhar – Haken – Ebeling theory of the Benard effect to explain the observed experimental results. Тhis model can be successfully used to explain hydro and aerodynamic problems only. In connection with this, a cascade model of the phased excitation of chemical bonds in the saturation regime of excitation is proposed and analyzed. To explain the experimental results, a phase diagram of silicon is used, according to which it has four crystallographic modifications. It is shown that cascade model more adequately describes the features of the appearance of surface structures, including a large scatter in the heights of the structures obtained and the appearance of new phases.